Montgomery‐Åsberg Depression Rating Scale factors in treatment‐resistant depression at onset of treatment: Derivation, replication, and change over time during treatment with esketamine. Issue 4 (24th June 2022) - Borentain, Stephane; Gogate, Jagadish; Williamson, David; Carmody, Thomas; Trivedi, Madhukar; Jamieson, Carol; Cabrera, Patricia; Popova, Vanina; Wajs, Ewa; DiBernardo, Allitia; Daly, Ella J.
Abstract: Objective: Derive and confirm factor structure of the Montgomery‐Åsberg Depression Rating Scale (MADRS) in patients with treatment‐resistant depression (TRD) and evaluate how the factors evident at baseline change over 4 weeks of esketamine treatment. Methods: Two similarly‐designed, short‐term TRANSFORM trials randomized adults to esketamine or matching placebo nasal spray, each with a newly‐initiated oral antidepressant, for 4 weeks (TRANSFORM‐1: N  = 342 patients; TRANSFORM‐2: N  = 223 patients). The factor structure of MADRS item scores at baseline was determined by exploratory factor analysis in TRANSFORM‐2 and corroborated by confirmatory factor analysis in TRANSFORM‐1. Change in MADRS factor scores from baseline (day 1) to the end of the 28‐day double‐blind treatment phase of TRANSFORM‐2 was analyzed using a mixed‐effects model for repeated measures (MMRM). Results: Three factors were identified based on analysis of MADRS items: Factor 1 labeled affective and anhedonic symptoms (apparent sadness, reported sadness, lassitude, inability to feel), Factor 2 labeled anxiety and vegetative symptoms (inner tension, reduced sleep, reduced appetite, concentration difficulties), and Factor 3 labeled hopelessness (pessimistic thoughts, suicidal thoughts). The three‐factor structure observed in TRANSFORM‐2 was verified in TRANSFORM‐1. Treatment benefit at 24 h with esketamine versus placebo was observed on all 3 factors and continued throughout the 4‐week double‐blind treatment period. Conclusions: A three‐factor structure for MADRS appears to generalize to TRD. All three factors improved over 4 weeks of treatment with esketamine nasal spray.